Regional development as a stimulator of competitiveness of the Polish economy - Życki, Artur (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
The author summarizes the implementation of regional policy 15 years after Poland’s accession to the EU as revealed in the official data coming from Polish regions, the Ministry of Investment and Development, the European documents and his own expert experience. Not only does he indicate the legitimacy of the adopted directions of intervention, but also he analyses the examples of misuse of EU funds. The latter cases, according to the author, are often associated with local politics, when investment decisions are based on current electoral calculations, and not long-term development strategy. The recommendations propose a change of the hitherto dominant compensatory model of the implementation of European funds to a modernisation model using knowledge as the main development component. This is also related to the need for a broader involvement of the academic community in regional policy.

Autor, opierając się na oficjalnych danych z polskich regionów, Ministerstwa Inwestycji i Rozwoju oraz dokumentów europejskich i własnych doświadczeniach eksperckich podsumowuje wdrażanie polityki regionalnej po 15. latach od akcesji Polski do UE. Wskazuje na zasadność przyjętych kierunków interwencji, ale też poddaje analizie przykłady niewłaściwego wykorzystania unijnych środków. Te ostatnie przypadki, zdaniem autora, często związane są z samorządową polityką, kiedy decyzje inwestycyjne wynikają z bieżącej kalkulacji wyborczej, a nie długofalowej strategii rozwoju. W rekomendacjach zaproponowano zmianę dominującego dotychczas wyrównawczego modelu implementacji europejskich środków na model modernizacyjny z wykorzystaniem wiedzy jako głównego składnika rozwojowego. Wiąże się z tym również potrzeba szerszego zaangażowania w politykę regionalną środowiska akademickiego.
Rozwój regionalny stymulatorem konkurencyjności Polskiej gospodarki
Keywords: cohesion policy; the Structural Funds; European integration; infrastructure investments; government; polityka spójności; fundusze strukturalne; integracja europejska; inwestycje infrastrukturalne; rząd